Eksplorasi Faktor-Faktor Pendorong Online Repurchase Intention di E-Commerce - Dellarianti, Rahma; Setiyaningrum, Ari (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to explore the driving factors of consumers online repurchase intention in e-commerce. In this research, the author examines whether factors such as effort expectancy, performance expectancy, and self-efficacy have a direct or indirect impact on online repurchase intention in e-commerce through the mediating role of satisfaction. The researcher collected primary data by distributing questionnaires to 147 individuals who met the criteria of having made at least one online purchase using an e-commerce application. The research findings, using SEM-PLS analysis, indicate that only satisfaction was found to have an impact on online repurchase intention, while effort expectancy, performance expectancy, and self-efficacy did not have a significant effect on online repurchase intention. Performance expectancy and self-efficacy were found to influence satisfaction, while effort expectancy had no impact on satisfaction. The mediation analysis results show that satisfaction mediates the effect of performance expectancy and self-efficacy on repurchase intention; however, satisfaction does not mediate the effect of effort expectancy on repurchase intention.